First quality score for referral letters in gastroenterology—a validation study. Issue 10 (8th October 2016) - Eskeland, Sigrun Losada; Brunborg, Cathrine; Seip, Birgitte; Wiencke, Kristine; Hovde, Øistein; Owen, Tanja; Skogestad, Erik; Huppertz-Hauss, Gert; Halvorsen, Fred-Arne; Garborg, Kjetil; Aabakken, Lars; de Lange, Thomas
Abstract : Objective: To create and validate an objective and reliable score to assess referral quality in gastroenterology. Design: An observational multicentre study. Setting and participants: 25 gastroenterologists participated in selecting variables for a Thirty Point Score (TPS) for quality assessment of referrals to gastroenterology specialist healthcare for 9 common indications. From May to September 2014, 7 hospitals from the South-Eastern Norway Regional Health Authority participated in collecting and scoring 327 referrals to a gastroenterologist. Main outcome measure: Correlation between the TPS and a visual analogue scale (VAS) for referral quality. Results: The 327 referrals had an average TPS of 13.2 (range 1–25) and an average VAS of 4.7 (range 0.2–9.5). The reliability of the score was excellent, with an intra-rater intraclass correlation coefficient (ICC) of 0.87 and inter-rater ICC of 0.91. The overall correlation between the TPS and the VAS was moderate (r=0.42), and ranged from fair to substantial for the various indications. Mean agreement was good (ICC=0.47, 95% CI (0.34 to 0.57)), ranging from poor to good. Conclusions: The TPS is reliable, objective and shows good agreement with the subjective VAS. The score may be a useful tool for assessing referral quality in gastroenterology, particularly important when evaluating the effect of interventions to improve referral quality.